2022
DOI: 10.1210/jendso/bvac097
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy May Be a Predictor of Stroke in Patients With Diabetes Mellitus

Abstract: BACKGROUND To investigate a conclusive relationship between diabetic retinopathy (DR) and the risk of stroke, we performed a meta-analysis of the available relevant studies. METHODS After a systematic search of studies in electronic databases, we screened all studies reporting the risk of DR status and stroke incidence and calculated their odds ratios (ORs) and hazard ratios (HRs). The effects of type of diabetes and severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…blindness [8]. Moreover, it has to be noted that PDR is considered an independent predictor of other severe diabetic complications such as ischemic stroke [9][10][11]. Contextually, a "domino effect" is characteristic for the cascading DM complications with a key role of DR as the early indicator of impaired molecular and visual signaling (Fig.…”
Section: Preamblementioning
confidence: 99%
See 1 more Smart Citation
“…blindness [8]. Moreover, it has to be noted that PDR is considered an independent predictor of other severe diabetic complications such as ischemic stroke [9][10][11]. Contextually, a "domino effect" is characteristic for the cascading DM complications with a key role of DR as the early indicator of impaired molecular and visual signaling (Fig.…”
Section: Preamblementioning
confidence: 99%
“…Diabetes-related microvascular complications are widely acknowledged as a risk factor for the macrovascular sequelae of stroke [9]. Moreover, it has to be noted that according to the metaanalysis of 19 studies involving 45,495 patients, people with diabetes who have DR have an elevated stroke risk-a relationship that was significant for patients with T2D but inconclusive for patients with T1D [10]. Studies reviewed by Hu et al have demonstrated that stroke risk increases as DR stage and lesion severity increase [52].…”
Section: Dr and Strokementioning
confidence: 99%
“…According to particular research, persons with diabetes have a much higher risk of stroke than those who do not have the disease. Additionally, several analysts concluded that having DR increases the risk of stroke in people living with diabetes [8]. Consequently, routine DR screening should be carried out.…”
Section: Review Drmentioning
confidence: 99%
“…Consequently, routine DR screening should be carried out. Optical coherence tomography (OCT) helps assess and control the risk of stroke; additional ophthalmological procedures include angiography and scanning laser ophthalmoscopy examination [8]. The stages of DR and its clinical findings are mentioned in Table 1.…”
Section: Review Drmentioning
confidence: 99%
See 1 more Smart Citation